Partial LRR over complete LRR: a preferable option - an FEA study of A - B trochlear dysplasia with critical abnormalities of patella alta and TT – TG value - Wang, Hanyu; Tahir, Elena; Wang, Huida; Zhang, Zhi; Ma, Xing (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThis study analyzed the effects of medial patellofemoral ligament (MPFL) injury and varying degrees of lateral retinacular release (LRR) on patellofemoral joint (PFJ) contact pressure using finite element analysis (FEA).MethodsA PFJ FE model was developed and validated at four knee flexion angles (0°, 30°, 60°, and 90°) using imaging data from a patient with A-B trochlear dysplasia and critical abnormalities of patella alta and tubercle-trochlear groove (TT-TG) value. MPFL injury was simulated by inhibiting its function, while LRR was modeled by adjusting the stiffness of the lateral retinaculum. Changes in PFJ contact pressure were systematically analyzed.ResultsAt 0° flexion, LRR led to increased PFJ pressure with an intact MPFL, whereas it resulted in a reduction with a ruptured MPFL. At 30° flexion, partial LRR didn’t elevate PFJ pressure when MPFL was intact, while complete LRR did with both intact and ruptured MPFL. At 60° flexion, partial LRR effectively reduced PFJ pressure, but complete release reversed this effect. At 90° flexion, PFJ pressure increased with the extent of LRR, irrespective of MPFL integrity. Specifically, complete LRR led to an increase in medial pressure, resulting in a shift of the pressure center from lateral to medial at 30° and 60° flexion.Clinical ImplicationsThis study provides new theoretical basis for the expected outcomes of varying degrees of LRR, which helps clinicians better conduct preoperative planning, especially in avoiding over - aggressive LRR procedures which may not yield improved outcomes.ConclusionIn patients with A- B trochlear dysplasia and critical abnormalities, excessive LRR does not consistently lower PFJ pressure but rather increases medial compartment pressure, suggesting that partial release may be a more effective and precise surgical approach in these patients.